THE TRAINING CONTENT OF PERSONS INVOLVED IN THE TRANSPORTATION OF DANGEROUS GOODS (Perner's Contacts, 2010)
The paper deals with the content structure and training time limits of safetyadvisors and drivers of vehicles carrying dangerous goods. It presents theprinciples and the validity of the certificates of training undertaken. Thearticle points to the need for training more other people from the businesssector and from government.
Keywords: dangerous thing; safety advisor; training; certification; theoretical training; basic training; specialized training